Extractive deep desulfurization of diesel using choline chloride-glycerol eutectic-based ionic liquid as a green solvent - Mohd Zaid, H.F. (Elsevier Ltd, 2017)
Today there are serious regulations to reduce the sulfur content of fuel because the SOx produced during the combustion of fuel containing sulfur species make the air polluted and have dangerous environmental impacts. With the aim to replace the present volatile, flammable and toxic organic solvents or inefficient, corrosive and expensive ionic liquids (ILs), the choline chloride-glycerol (ChCl-G) eutectic-based ionic liquid (EIL) was introduced as a green, effective, non-toxic, non-corrosive and also recyclable for extractive desulfurization (EDS) of oxidized dibenzothiophene (DBTO2) from model oil in this work for the first time. ChCl-G showed excellent sulfur removal and it showed a high extraction efficiency of 97.06 within 20 min. Using ChCl-G, the DBTO2 concentration was reduced from 100 ppmw to 0 ppmw within two extraction cycles achieving deep desulfurization. Effect of some important parameters including stirring speed, extraction time, ChCl-G:oxidized model oil filtrate volume ratio, multistage extraction and sulfur species (DBTO2 and oxidized 4,6-dimethyldibenzothiophene (4,6-DMDBTO2)) were investigated. It was found that the optimum condition for EDS were stirring speed of 300 rpm, 20 min of extraction time, 1:5 ChCl-G:oxidized model oil filtrate volume ratio and two cycles of extraction. The feasibility of ChCl-G for extraction of different sulfur species was observed in the order of DBTO2 > 4,6-DMDBTO2. The spent ChCl-G was regenerated and showed an extraction efficiency of 88.34 within 3 cycles. The results of the present work hopefully provide useful information for further industrial application of ChCl-G as an efficient green solvent for EDS of diesel fuel. © 2016 Elsevier Ltd